Recent Advances in the Management of End-Stage Renal Disease (ESRD) in Children - Richard N. Fine (Indonesian Pediatric Society, 1988)
It has been almost 20 years since the initial report were published detailing the use of the dual treatment modalities of dialysis and renal transplantation to treat children with ESRD. During this time, the outlook for the infant, child and adolescent with ESRD has changed dramatically from abject pessimism to cautious optimism. Initially, hemodialysis was the principle dialytic technique utilized; however, intermittent peritoneal dialysis was used occasionally in selected centers. The latter required less technical expertise, but necessitated considerably more dialysis time and was significantly less efficient at alleviating the clinical and biochemical consequences of uremia.